School Geography under COVID-19: Geographical Knowledge in the German Formal Education - Péter Bagoly-Simó; Johanna Hartmann; Verena Reinke (Tijdschrift voor economische en sociale geografie, 2020)
This paper aims to explore some of the changes affecting the teaching and learning of secondary geography as a result of the COVID-19 pandemic. In doing so, it sets a focus on geographical knowledge and its alteration in times of extraordinary measures to diagnose its challenges. Against the background of current debates on competence- and standard-based education from the sociology and history of education as well as from geography education, problem-centred interviews served to explore the perspectives of 15 German secondary school teachers on the alterations their Geography teaching suffered since the COVID-19 lockdown. Analytical categories were general challenges, communication with stakeholders, educational media usage, and the role of COVID-19 in geographical knowledge acquisition. The results uncovered, along with systemic challenges, two main areas in need of consideration to redefine subject-specific knowledge in times of competence-based education, namely geography teachers' professional identity and perspectives on the role of geographical competencies.
Keywords: 330; Geography education; Germany; interview; COVID-19; geographical knowledge; powerful knowledge